COMPLEX TREATMENT OF PERIODONTITIS IN SYSTEMIC LUPUS ERYTHEMATOSUS - Luchyn, I.I.; Kryvanych, A.V.; Skulska, S.V.; Kotelevskyi, R.A.; Chebotar, O.A.; Zhero, N.I.; Shnaider, K.S. (World of Medicine and Biology, 2024)
The research is devoted to the implementation of an integrated approach to treatment to improve the quality of life of patients with periodontitis in systemic lupus erythematosus with the determination of quantitative changes in transcutaneous tension before and after treatment. The study involved 50 patients with systemic lupus erythematosus (10 men and 40 women) aged 20 to 55 years (mean age 38.8±7.6 years) who were treated in the rheumatology department. During treatment, patients were divided into two groups by blind randomisation. The first group received only systemic drug and local treatment of periodontitis. The second group received systemic treatment of systemic lupus erythematosus, local therapy and laser therapy on the gum area. A quantitative comparison of patients in group I before and after treatment revealed that in mild systemic lupus erythematosus, the regional perfusion index increased by 30 % in the lower jaw, and in severe lupus erythematosus, only by 28 %. In a quantitative comparison of patients in group II before and after treatment, the regional perfusion index increased to 46 % in mild systemic lupus erythematosus and to 29 % in severe lupus erythematosus.